Topical gentamicin for the prevention of tunneled hemodialysis catheter-related infections: a randomized double-blind study - Caetano, Camille Pereira [UNESP]; Cassimiro, Vanessa Piacitelli [UNESP]; Dionisio, Daniele Lopes [UNESP]; Pereira, Viviane Pollo [UNESP]; Rodrigues, Elisabete Aparecida Crispim [UNESP]; Rosa, Priscila Nunes [UNESP]; Elias, Daniele Aparecida [UNESP]; Ponce, Daniela [UNESP] (Oxford University Press (OUP), 2023)
Introduction: Infection is the second leading cause of death in dialysis patients, with catheter-related bloodstream infection being the most serious. Exit Site Infection and Tunnel Infection are also related to the catheter. Objective: To compare the infection rates achieved with the application of either topical gentamicin or placebo to the exit-site of tunneled catheters filled with locking solution in chronic hemodialysis patients. Methods: This randomized double-blind clinical trial compared the application of 0.1% gentamicin versus placebo to the exit site of tunneled hemodialysis catheters filled with a prophylactic locking solution. A total of 91 patients were randomly allocated to 2 groups: placebo or 0.1% gentamicin. Results: Mean patient age was 60.4 (+ 15.3) years, with predominance of males (60.4%). The main cause of chronic kidney disease was diabetes (40.7%). The rates of exit site infection (placebo = 30% vs. gentamicin = 34.1%, p = 0.821), and bloodstream infection (placebo = 22% vs. gentamicin = 17.1%, p = 0.60), as well as both exit site infection and bloodstream infection incidence density per 1000 catheter-days (p = 1) did not differ between groups. The infection-free curve was also similar in both groups. Conclusion: The application of topical 0.1% gentamicin to the exit site of tunneled catheters filled with lock solution did not reduce infectious complications when compared to topical placebo in patients on chronic hemodialysis. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Catheter-related infections; Central venous catheters; Hemodialysis; Tunneled catheter